REDUCED INSECTICIDE APPLICATIONS CAN ENHANCE NATURAL ENEMIES OF BEMISIA TABACI IN COTTON - NAZIR, JAVARIA; SHAKEEL, MUHAMMAD ARSHAD; SALEEM, MUHAMMAD ASAD; QAYYUM, MIRZA ABDUL; NAZ, IFFAT (Innovare Journal of Agricultural Sciences, 2022)
Excessive amount of insecticides destroys natural enemies of cotton pests and consequently the population of whitefly flares up. The present research focused on the use of PB ropes to reduce application of insecticides and to investigate the ecological impact on Bemisia tabaci and beneficial fauna in cotton fields. Two cotton varieties (BS-15 and NIAB-878) were sown in research area of MNS University of Agriculture, Multan during 2018 on 30 acres. PB ropes dispensers (PB-ropes L®) were installed at 120/acre at pin head square stage of cotton. It was observed that application of PB ropes reduced need for insecticide applications, thus helped conservation of beneficial fauna in cotton fields throughout the season, which kept whitefly populations below EIL. Population of whitefly nymph was reduced after application (0.9/leaf-seasonal average) in PB ropes treated fields as compared to untreated check (8.1/leaf-seasonal average). Furthermore, higher population of green lacewing (4.00/plant) was observed in PB ropes treated field. It was concluded that populations of whiteflies were kept below EIL due to conservation of green lacewing. This positive effect of PB ropes is presumably due to increasing the number of cotton insect pest biological agents. This indirect effect of mating disruption (PB ropes) is of great value within the framework of IPM in cotton.